2022
DOI: 10.1016/j.puhe.2022.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression, anxiety and stress among adults during the COVID-19 pandemic in Southern Switzerland: the Corona Immunitas Ticino cohort study

Abstract: Objectives. Using longitudinal data from Southern Switzerland we assessed ten-month temporal trajectories of moderate-to-severe depression, anxiety and stress among adults after the first pandemic wave and explored differences between socio-demographic and health status groups. Study design. Population-based prospective cohort study. Methods. Participants were 732 (60% women) adults aged 20–64 who completed the Depression, Anxiety and Stress Scale on a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
4
14
0
Order By: Relevance
“…In the European studies analyzed, the female gender was found to be significantly more at risk than the male for the development of stress and anxiety, depression [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], and post-traumatic symptoms [ 79 , 80 , 81 ]. The evolution of symptoms over time was also worse for women [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the European studies analyzed, the female gender was found to be significantly more at risk than the male for the development of stress and anxiety, depression [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], and post-traumatic symptoms [ 79 , 80 , 81 ]. The evolution of symptoms over time was also worse for women [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have reported the trajectory of mental health among adults during the early stage of the COVID-19 pandemic ( Fluharty et al, 2021 ; Piumatti et al, 2022 ). However, our study assessed psychological well-being on a long-term basis among older adults and classified its trajectory patterns for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several studies have administered multiple surveys to evaluate the trajectories of mental health. Piumatti et al (2022) administered a monthly survey following the first wave of the pandemic, from August 2020 to May 2021, which showed that depression, anxiety, and stress increased among adults in Southern Switzerland ( Piumatti et al, 2022 ). By contrast, Fluharty et al (2021) reported that both depressive and anxiety symptoms decreased over time among adults during the first 21 weeks of the COVID-19 lockdown in the United Kingdom ( Fluharty et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elderly and chronically ill patients were more likely to experience emotional disturbances related to protective measures, such as confinement and social isolation [ 36 , 37 ]. However, it is in this social profile where we find a greater monitoring of protection measures.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients and those with chronic diseases have the highest adherence to health recommendations to prevent infection [ 38 ]. Some authors point out that these measures generate stress and anxiety in this profile of people [ 36 , 37 ]. Although patients who overcome SARS-CoV-2 infection may maintain impairments, such as respiratory or cognitive problems [ 39 ], people who have already passed COVID-19 show a lower likelihood of meeting compliance measures.…”
Section: Discussionmentioning
confidence: 99%